The effect of nutritional education program on micronutrient intake in children with chronic liver disease: A clinical trial - Zahra Namjou; Seyed Ali Jafari; Aramesh Rezaeian; Majid Ghayour-Mobarhan; Samira Nasrfard (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Chronic liver disease (CLD) is one of the most common chronic diseases in the world that threatens the health of children due to its many complications such as malnutrition and problems related to growth and development. Paying attention to nutrition and lifestyle modification in these children is of special importance. Therefore, the aim of this study was to determine the effect of nutritional education program on micronutrient intake in children with CLD. MATERIALS AND METHODS: The present study is a two-group randomized clinical trial that was performed by available sampling and referred to Ghaem Children's Hospital in Mashhad in 2016. In this study, 77 children with CLD who met the inclusion criteria (45 children in the intervention group and 32 children in the control group) were studied. The intervention included six workshops and training on proper diet, post-workshop phone calls, and regular face-to-face counseling sessions (first 4 weeks once a week and second 4 weeks once every 2 weeks) on adherence to the above diet. Patients in the control group received routine care. The collection tools in the study included demographic information questionnaires, body composition device, and diet plan form in the form of 24-h recall forms. Data analysis was performed using descriptive statistical tests and Mann-Whitney and Wilcoxon statistical tests using SPSS software version 16. RESULTS: Based on the results of the study, the mean age of the research units was 7.8 ± 3.6 years. The mean duration of CLD was 4.6 ± 1.8 years in the intervention group and 5.1 ± 1.9 years in the control group. The mean crude intake of most minerals after the intervention was significantly higher than before the intervention, except for the crude intake of retinol, thiamine, riboflavin, folate, Vitamin C, iodine, and Vitamin B12. Furthermore, in relation to the modified intake of micronutrients, the mean modified intake of most micronutrients after the intervention showed a significant increase compared to before, except for retinol, Vitamin D, niacin, B12, and iodine. CONCLUSION: Considering the effect of providing a nutritional education program to improve micronutrient intake in children with CLD and emphasizing the importance of adequate micronutrient intake in improving the health of children, special nutrition programs should be provided to these children with special attention. In this regard, nurses can play an important role in improving the quality of nutrition of children by providing nutrition programs with appropriate follow-up.